A systematic review and meta‐analysis of laparoscopic vs open restorative proctocolectomy. (30th July 2013) - Singh, P.; Bhangu, A.; Nicholls, R. J.; Tekkis, P.
Abstract Aim The benefits of a laparoscopic approach to restorative proctocolectomy (RPC) are controversial. The aim of this meta‐analysis was to compare the outcome following laparoscopic and open RPC, with particular attention to adverse events and long‐term function. Method A systematic search of the MEDLINE, EMBASE and Ovid databases was performed for studies published until March 2012. The primary end‐point was long‐term function. Secondary end‐points were intra‐operative details, short‐term postoperative outcome and postoperative adverse events. Weighted mean difference (WMD) and odds ratio (OR) were calculated using fixed/random effect meta‐analytic techniques. Results The final analysis included 27 comparative studies of 2428 patients, of whom 1097 (45.1%) underwent laparoscopic surgery. A laparoscopic approach was associated with a significantly longer operation time (WMD 70.1 min, P < 0.001), shorter length of hospital stay (WMD −1.00 day, P < 0.001), reduced intra‐operative blood loss (WMD −89.10 ml, P < 0.001) and a lower incidence of wound infection (OR 0.60, P < 0.005). No significant differences were observed in the rate of pouch failure. Although there was no significant difference in the number of daily bowel movements (OR 0.04, P = 0.950), laparoscopic surgery led to fewer nocturnal bowel movements (WMD −1.14, P < 0.001) and reduced pad usage during the day (OR 0.22, P < 0.001) and night (OR 0.33, P < 0.001). The post hoc power to detect differences in adverse event rates ranged from 5% to 42%. Conclusion Laparoscopic and open approaches to RPC produced equivalent adverse event rates and long‐term functional results. However, the present evidence is underpowered to detect true differences in adverse event rates.